New Zealand as an Investment Destination (The Australasian Institute of Mining and Metallurgy, 1997)
Last evening, in Auckland, I heard the Chairman of Heinz US, Dr Tony O'Reilly (who, in addition to Heinz's ownership of our largest food processor, also has substantial personal investments in this country), advocate New Zealand as a 'regional corporate capital'.   Why would someone like Dr O'Reilly hold that view? No doubt, as one of Ireland's great rugby players of the 50s and 60s, he admires at least one thing that we do very well (confirmed again in Dublin over the past weekend). But that's not sufficient to support such a view.   He cited many reasons for preferring New Zealand over, say, Sydney, Australia, calling this 'the most rational in which to locate [an] international headquarters', including û +         we have no capital gains tax; +         a more 'pro-business environment'; +         a 'first class' legal and banking system; and +         a 'simple political system'.   I can find no better 'text for today's address.